2010
DOI: 10.1021/jo1019688
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of All the Known Phlegmarine Alkaloids

Abstract: The asymmetric synthesis of all four of the known natural phlegmarines and one synthetic derivative has been accomplished in 19 to 22 steps from 4-methoxy-3-(triisopropylsilyl)pyridine. Chiral N-acylpyridinium salt chemistry was used twice to set the stereocenters at the C-9 and C-2′ positions of the phlegmarine skeleton. Key reactions include the use of a mixed Grignard reagent for the second N-acylpyridinium salt addition, zinc/acetic acid reduction of a complex dihydropyridone, and a von Braun cyanogen brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The putative (I) and natural huperzine (1) are clearly differentiated by their 13 C NMR data: (i) the chemical shifts of C (2) and C(4) are more deshielded (8 and 11 ppm, respectively) in 1 (Figure 2). These data suggest that huperzine N has a trans-decahydroquinoline ring core instead of the cis-ring fusion originally Comins, 8 who also reported the synthesis of three related alkaloids bearing different substituents at the two nitrogen atoms, while Takayama 9 achieved lycoposerramine X. The key challenges in the synthesis of these alkaloids are the generation of the trans-decahydroquinoline core and the stereocontrol in the genesis of the stereocenter at C-5 where the pyridylmethyl backbone is attached (Scheme 1).…”
Section: Stereoparentsmentioning
confidence: 91%
“…The putative (I) and natural huperzine (1) are clearly differentiated by their 13 C NMR data: (i) the chemical shifts of C (2) and C(4) are more deshielded (8 and 11 ppm, respectively) in 1 (Figure 2). These data suggest that huperzine N has a trans-decahydroquinoline ring core instead of the cis-ring fusion originally Comins, 8 who also reported the synthesis of three related alkaloids bearing different substituents at the two nitrogen atoms, while Takayama 9 achieved lycoposerramine X. The key challenges in the synthesis of these alkaloids are the generation of the trans-decahydroquinoline core and the stereocontrol in the genesis of the stereocenter at C-5 where the pyridylmethyl backbone is attached (Scheme 1).…”
Section: Stereoparentsmentioning
confidence: 91%
“…16 On the other hand, the building block 6 for the synthesis of Lycopodium alkaloids 17 was converted into alkene 8 via enol triflate for-mation followed by reduction. 18 Due to the steric hindrance of 8, the reaction required more time but fortunately competitive reduction of the alkene was minimal. Regioselective coupling with pyridine 1h gave 9 along with its epimer (dr 2:1) The achievement of compound 9 constitutes a formal synthesis of Serratezomine E, as we have previously demonstrated that intermediate 9 can be converted to this Lycopodium alkaloid in a few steps.…”
Section: Table 2 Scope Of the Alkene Componentmentioning
confidence: 99%
“…The coupling between hydrazone 1b and alkene 2j gave compound 5i , which is a precursor of the pharmaceutical compound methamphetamine . On the other hand, compound 6 , a building block for the synthesis of Lycopodium alkaloids, was converted into alkene 8 via enol triflate formation followed by reduction . Because of the steric hindrance of 8 , the reaction required more time, but fortunately, competitive reduction of the alkene was minimal.…”
mentioning
confidence: 99%
“…16,19-22 It is reasonable to presume that excess pyridine then readily adds to the chloroformate to generate the putative N -acylpyridinium ion intermediate 19 . 26-28 This carbonyl activation increases the reactivity at the electrophilic secondary carbon center, which allows for S N 2 nucleophilic substitution by chloride ions. This process releases CO 2 and pyridine, while generating the alkyl chloride with an inversion of stereochemistry.…”
Section: Resultsmentioning
confidence: 99%